Pseudomonas aeruginosa strain PA01 impairs enzymes of the phosphotransfer network in the gills of Rhamdia quelen - Baldissera M.D. (2017)
© 2017 Elsevier B.V.Integration of mitochondria with cytosolic ATP-consuming/ATP-sensing and substrate supply processes is critical for gills bioenergetics, since this tissue plays an important role in the respiratory energy metabolism. The effects of bacterial infection on gills remain poorly understood, limited only to histopathological analyses. Thus, the aim of this study was to investigate whether experimental infection by Pseudomonas aeruginosa strain PA01 alters the enzymes of the phosphoryltransfer network (adenylate kinase (AK), pyruvate kinase (PK) and cytosolic and mitochondrial creatine kinase (CK)) in gills of silver catfish (Rhamdia quelen). The animals were divided into two groups with six fish each: uninfected (negative control) and infected (positive control). On day 7 post-infection (PI), animals were euthanized and the gills collected. AK, PK, and cytosolic and mitochondrial CK activities in gills decreased in infected compared to uninfected animals. Also, severe gill damage and destruction in the primary and secondary lamellae was observed in the infected animals. Therefore, we have demonstrated, for the first time, that experimental infection by P. aeruginosa inhibits key enzymes linked to the production and utilization of metabolic energy in silver catfish, and consequently, impairs cellular energy homeostasis, which may contribute to disease pathogenesis.